A metafrontier analysis of determinants of technical efficiency in beef farm types: An application to Botswana - Bahta, Sirak T.; Baker, Derek; Malope, P.; Katjiuongua, Hikuepi B. (2015)
The study used a stochastic metafrontier model followed by a Tobit regression model to estimate technical efficiency and meta-technology ratios and assess factors influencing efficiency of a suite of beef farm types in Botswana. Results show that the average technical efficiency level is 0.496 for the whole sample and 0.355, 0.463 and 0.571 for beef farms who engage in cattle only, cattle and crop, and cattle, crop and small stock farming, respectively. Considerable scope is identified for improving beef production in Botswana, and targeting is enabled by the differential results across the farm types. Policy analysis using models that assume different beef farm types operate under similar technology are therefore presenting a misleading picture. Considering the importance of livestock sector in poverty reduction, there is a need for appropriate policies directed towards enhancing efficiency. Especially, such policies should be targeted on provision of technology-related services such as controlled breeding methods.